Arab male physicians' perceptions about their own smoking behaviors: a qualitative study - Samira Obeid; Nasra Idilbi; Abed Agbarya; Hanna Admi (BMC, 2024)
Abstract Background Smoking remains the leading preventable cause of disease, disability, and death worldwide. Although physicians have high levels of health literacy with awareness of the consequences of smoking and their essential role in smoking cessation of patients, some physicians continue to smoke. Rates of smoking among Arab male physicians are high. This study aimed to gain insights into Arab male physician's perceptions of their own smoking behaviors and their professional role in health promotion. Methods Using purposive sampling, we recruited 25 Arab male physicians working in hospital and community clinic settings who currently smoke. Semi-structured, hour-long, interviews were held during January-June 2022. We then performed a thematic analysis of the interview data. Results The analysis revealed three categories, two sub-categories, and 15 emerging themes. The category 'Antecedents: prior to becoming a physician' revealed the themes: smoking experience during adolescence; social and ethnic culture; stress during medical studies; and on & off periods of quitting smoking. The category 'Physicians' perception of smoking' was sorted into two sub-categories: (1) Personal aspects, including the themes 'relaxation from stress', 'self-compensation', 'addiction', and 'enjoyable experience', and (2) Professional aspects, including the themes 'lack of knowledge about cessation', 'inadequate workplace support', 'motivation to consult patients', and 'awareness of their role as primary care physicians'. The category'Impacts' revealed the themes 'personal health and well-being', 'professional competence', and 'professional image in public'. Conclusions This study provides an in-depth understanding of the personal, socio-cultural, and professional aspects of the phenomenon of Arab male smoking physicians from their perspective. Based on this information, we recommend developing programs that support and empower all physicians to cope better with their personal and professional stress as well as instituting programs that will provide all physicians with specific knowledge and skills related to smoking cessation. These programs should improve the ability of physicians to serve as positive role models for their patients for preventing and ceasing smoking, thus enhancing the image of the medical profession and, most importantly, improving the health of the public.